From Bengal to Java: Raffles’ Landrente in Indonesian Agrarian System - Juwono, Harto (Indonesian Historical Studies, 2023)
The issues of land ownership taxes hold in a distinctive position within Indonesian legal framework, with historical roots extending from Indonesia’s Independence to the colonial era. Originating during the British ruled Java from 1811 to 1816, British Lieutenant Governor-General Thomas Stamford Raffles introduced the concept of landrente for a tax on land. This study endeavors to explore the historical evolution of land ownership taxes with the Indonesian legal system, tracing its inception from the colonial era to contemporary times. The historical method based on archival materials, legal documents and historical records, have been employed. After criticizing the archival sources that used, the interpretation will be applied for getting some historical facts. Based on these facts, reconstruction as a final phase of the method will be built. A comprehensive historical overview of the evolution of land ownership taxes in Indonesia has been revealed, traversing the colonial period to contemporary times. The transition from landrente to grondbelasting marks a pivotal shift in tax principles and individual property rights. The underlying principle is the fact that all land was owned by government, while the people could only work on. As a form of rent for the land, the people had to give a part of the proceeds to the government. Collection system followed the system that used by The British East India Company in Bengal, namelythrough the zamindar. In Java, Raffles submitted to the colonial officials in the local level.